Synergistic impact of aflatoxin and ochratoxin A exposure in Charles foster rats: a toxicological study - Kanchan Gopal Choudhary; Choudhary Sharfuddin; Arun Kumar; Ashok Kumar Ghosh (Discover Toxicology)
Abstract Aflatoxin (AF) and Ochratoxin A (OTA) are potent dietary contaminant of agrarian products, leading to hepatotoxicity and nephrotoxicity. The current study aims to evaluate the sub-acute toxicity impact of AF and OTA on Charles Foster rats. A total of n = 40, adult male rats were randomly divided into ten groups; a control group, a 30 days, 45 days and 60 days treated groups of orally administered 0.9 mg/kg body wt./day of AF, 2.75 mg/kg body wt/day of OTA and (0.45 + 1.375) mg/kg body weight/day of AF + OTA. There were significant alterations observed in the blood chemistry with normocytic anemia in AF and OTA treated groups. There was significant increase in liver function tests such as AST and ALP with significant increase in the Kupffer cells in the liver of AF and OTA treated groups. In AF + OTA significant elevation of AST only observed. There were significant histopathological changes observed in liver tissue in all the treated groups which are in correlation with biochemical analysis. The significant elevation in uric acid and creatinine levels is in correlation with nephrotoxicity in OTA treated group. There was initial significant elevation of creatinine observed only in 45 days treated group of AF + OTA. The histopathological analysis of AF + OTA shows chronic toxicity in kidney tissue. Taken together, this study indicates that AF induces significant biochemical and histological alterations in liver and OTA in kidney which significantly correlates with impaired qualitative and quantitative analysis. The biochemical changes are not in correlation with chronic nephrotoxicity observed in AF + OTA groups and hence it might act as silent toxicity.